Skill Development on the Shop Floor - Heading to a Digital Divide? - Kathleen Warnhoff; Patricia de Paiva Lareiro (Proceedings of the Weizenbaum Conference 2019 "Challenges of Digital Inequality - Digital Education, Digital Work, Digital Life", 2019)
In recent years, there has been a huge debate on how modern sensor technology and the increasing connectivity of production systems have changed industrial production processes and working conditions. This article contributes to the discussion on the effects of digitalization on skill development under different working conditions with the following question: How has learning in the work-process changed with the introduction of data-based technologies? To examine the interaction between digital assistance systems and organizational parameters on informal learning, we analyzed the implementation of digital assistant systems in two different groups: low-skilled assembly workers and high-skilled shop floor managers. Our findings suggest that a lack of autonomy in workplaces has negative impacts on informal learning and thus skill development. When the design of assistance systems perpetuates preexisting inequalities in the working conditions, their use can contribute to a polarization of qualifications and a digital divide of the workforce.
Keywords: 330; industry 4.0; digitalization; assistance systems; informal learning; skill development; digital divide